Turismo Gastronómico en la provincia de Cotopaxi - Guerrero Echeverría, Jessica Mercedes (2022)
This research focuses on gastronomic tourism in the province of Cotopaxi, since this is an important part of its traditions and cultural identity and gastronomic tourism, since over the years the preparation of its representative dishes have been changing and adapting to the current life. The research has a qualitative methodological approach, so that complete data are collected on the subject in order to analyze and interpret results based on the cultural and ideological aspects of the study area. In the first objective, primary and secondary information will be collected through the bibliographic review of books, scientific articles, magazines and the Provincial Government of Cotopaxi and in the repositories of the Ecuadorian Institute of Statistics and Census, where the current situation of the study area will be analyzed taking into account three aspects: economic, socioeconomic and environmental. In the second objective, the information will be collected through the inventory of intangible cultural heritage, applying the files of the National Institute of Cultural Heritage to know the manifestations and gastronomic heritage such as the variety of typical dishes. To fulfill the third objective, a gastronomic route will be designed and elaborated, using the data and systematized information of the inventory, so that it can be used as a tool of diffusion and a generating factor of gastronomic tourism in the province of Cotopaxi. . Keywords: Typical dishes, Gastronomic route, Gastronomic